2006
DOI: 10.1088/0031-9120/42/1/005
|View full text |Cite
|
Sign up to set email alerts
|

Assessing conceptual learning from quantitative problem solving of a plane mirror problem

Abstract: In recent years more emphasis has been placed on conceptual learning and understanding in the sciences. Unfortunately, among advocates of such a position there are those who do not see any role for quantitative problem solving at the secondary/high school level or even the introductory university level. This may be due to the frequent use of typical ‘plug and chug’ problems in problem solving sessions. However, a quantitative problem which requires students to illustrate their conceptual learning and understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Physics is a part of science that consists of theory, and the laws of physics are usually packed in the form of exact mathematical equations. Students in advanced physics mostly solve the laws of physics mathematically and apply them in different situations using simulation and experiment to be able to explain and predict phenomena (Mason & Singh, 2016b;Yap & Wong, 2007). In other words, to understand a physics concept, students must learn how to interpret and use logic for abstract physics principles and strive to create a coherent structure of knowledge.…”
Section: Problem Solvingmentioning
confidence: 99%
“…Physics is a part of science that consists of theory, and the laws of physics are usually packed in the form of exact mathematical equations. Students in advanced physics mostly solve the laws of physics mathematically and apply them in different situations using simulation and experiment to be able to explain and predict phenomena (Mason & Singh, 2016b;Yap & Wong, 2007). In other words, to understand a physics concept, students must learn how to interpret and use logic for abstract physics principles and strive to create a coherent structure of knowledge.…”
Section: Problem Solvingmentioning
confidence: 99%
“…This was also due to the students' inability to comprehend the physical and imaginative of images comprehensively. Yap and Wong [22] have shown that secondary school students have some conceptual problems related to the conventional mirror. Therefore, it would be useful for students to fully understand the construction issue of the image in the plane mirror.…”
Section: Discussionmentioning
confidence: 99%
“…It also shows which tool is efficient for the study purpose to propound rules and facts that can stand on their own regardless it is true or not (Daniel, 2016). Cohen (2011) debates that quantitative research is used in epistemology and ontology regarding human behavior which can be controlled (Yap & Wong, 2007). Accordingly, quantitative approaches use theory to generate data (Daniel, 2016).…”
Section: Research Methodological Choicementioning
confidence: 99%